Network analysis and traceability on Zcash blockchain - Koh, Justin Wei Xiang (Nanyang Technological University, 2021)
There is a common misconception that bitcoin transactions are private, but they are not private, they are anonymous. Zcash is a digital currency, or cryptocurrency, first developed in 2013 that aimed at using cryptography to provide enhanced privacy for its users compared to other cryptocurrencies such as Bitcoin. Zcash utilizes complex cryptographic protocols along with a widely distributed network of computers to encrypt transactions to disallow third parties from viewing specific details of its transaction. It has a unique method of writing transactions on the blockchain by utilizing two different types of addresses, transparent and shielded. In this study, we will explore some statistical and transactional analysis of the Zcash blockchain with the help of the GraphSense.